Pengaruh Faktor Daya Serap Terhadap Tumbuh Kembang Anak Melalui Lingkungan Pendidikan dan Pola Asuh Orang Tua - Septian Agustin; Jauhan Budiwan (Absorbent Mind, 2021)
This article aims to determine the character of the child in each development according to the maturity age and parenting style. Childhood is the richest period. This period should be utilized by educators as well as possible. This writing is done through literature study. The data collection tool in this research is to search journals contained in several electronic media such as digital libraries, the internet, through books. The data analysis technique used in this research is annotated bibliography which means a simple conclusion from an article, book, journal, or some other source of writing. The results of this writing. Child development is influenced by the child's absorption of the environment and parenting style. Children absorb from the environment in which they live and at the same time absorb the behavior of their parents as their daily figures. Child development is also influenced by the child's absorption of the education they receive at each stage of development. With the provision of high absorption power, each child is able to create their world in living and facing the various problems of their respective lives. This absorption capacity will shape the character and personality of children so that later they have the principles, lifestyle, paradigm, and values that they adhere to. Thus, the future of a child rests on each of the absorbent powers which they have had from birth and which are cultivated in their own way through the tasks at each stage of their development.